DETERMINAN KINERJA AUDITOR PADA PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) NUSA TENGGARA BARAT - RUSLI AMRUL; BAIQ KISNAWATI (GANEC SWARA, 2023)
This study aims to examine the effect of Professionalism, Independence, Motivation, Competence on Auditor Performance. The population in this study were auditor functional officers and BPKP functional officers involved in inspection and supervision activities at BPKP NTB Representatives. Data was obtained by distributing questionnaire links to respondents at the NTB BPKP Representative office, the number of respondents was 67 people in the NTB BPKP Representative office. Data were analyzed using multiple linear regression. The results show that professionalism has a positive and significant effect on auditor performance, motivation has a positive and significant effect on auditor performance, and competence has a positive and significant effect on auditor performance, while independence has a positive but not significant effect on auditor performance at BPKP NTB Representatives. The results of this study also show that the independent variables (professionality, independence, motivation and competence) are able to explain the dependent variable (auditor performance) by 73% while the remaining 27% of auditor performance is explained by other variables outside the variables studied.